2014
DOI: 10.3109/07420528.2014.986682
|View full text |Cite
|
Sign up to set email alerts
|

Dim light at night increases body mass of female mice

Abstract: During the past century the prevalence of light at night has increased in parallel with obesity rates. Dim light at night (dLAN) increases body mass in male mice. However, the effects of light at night on female body mass remain unspecified. Thus, female mice were exposed to a standard light/dark (LD; 16h light at ~150 lux/8h dark at ~0 lux) cycle or to light/dim light at night (dLAN; 16h light at ~150 lux/8h dim light at ~5 lux) cycles for six weeks. Females exposed to dLAN increased the rate of change in bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 19 publications
2
24
0
1
Order By: Relevance
“…Studies have shown that dim light at night can increase body weight in mice (Aubrecht et al 2014; Fonken et al 2013a; Kott et al 2012). In this study, rats that underwent TBI and received constant light exposure had a lower body weight than rats that underwent TBI with a normal LD cycle, suggesting that circadian disruption, which is associated with temporal alterations in feeding behavior, might inhibit post-TBI functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that dim light at night can increase body weight in mice (Aubrecht et al 2014; Fonken et al 2013a; Kott et al 2012). In this study, rats that underwent TBI and received constant light exposure had a lower body weight than rats that underwent TBI with a normal LD cycle, suggesting that circadian disruption, which is associated with temporal alterations in feeding behavior, might inhibit post-TBI functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Shift workers who work from 10 pm to 6 am make up about 20% of working force in modern society (Antunes et al, 2010) and have a higher prevalence of obesity and heart disease (Karlsson et al, 2001; Kubo et al, 2011; Suwazono et al, 2008). Dim light at night or prolonged daily light exposure promotes obesity and metabolic disorders in animal models (Aubrecht et al, 2015; Kooijman et al, 2015; Opperhuizen et al, 2015). Housing mice under constant light caused arrhythmicity in locomotor activity, increased food intake, reduced energy expenditure, increased body fat mass, and impaired insulin sensitivity (Coomans et al, 2013a; Shi et al, 2013).…”
Section: Evidence Supporting a Role Of Central Clock In Energy Metabomentioning
confidence: 99%
“…(56-58) One important point to keep in mind, however, is that the spectral and absolute sensitivities to light are species-specific. Animal work, therefore, can be only be translated to human models once these spectral and absolute sensitivities to light are taken into account.…”
Section: Introductionmentioning
confidence: 99%